What Happened When California Suspended Bail during COVID? - Deepak Premkumar; Andrew Skelton; Magnus Lofstrom; Sean Cremin (Institute of Labor Economics (IZA), 2025)
The efficacy and fairness of cash bail in promoting public safety has been a prominent policy question in recent years, but it is difficult to rigorously estimate the effects of bail, particularly at the state level, because of a lack of exogenous variation. California responded to the COVID pandemic by setting bail at zero dollars for many misdemeanors and felonies, increasing the number of people who were immediately released after being arrested. We separately estimate the impact of the implementation and revocation of these zero-bail orders on rearrests using a triple difference framework that relies on the staggered timing across counties and uses offenses that did not qualify for zero bail as a control group. The implementation of emergency bail orders significantly increased the likelihood and number of rearrests within 30 days of the initial arrest. The increase in rearrests was driven by felony offenses, but we find no evidence of an increase for violent felonies, a concern raised by some observers. For the counties that had an emergency bail order for at least a year, there was a statistically significant increase on rearrests initially, but the effect diminished over time. The average effect over the first year of implementation in these counties was not statistically significant. Notably, the rise in felony rearrests did not subside for these counties that extended an emergency order past 2020. Though the initiation of emergency bail orders led to increases in rearrests, lifting these orders had no significant effect on rearrests, regardless of offense type.
Keywords: K42; K14; I18; D73; H70; 330; bail; pretrial; COVID-19; rearrest; felony; misdemeanor; crime; violent; incapacitation